Ta‘līm al-Kitābah bi-isti‘māl Ṭarīqat al-Qawā‘id wa al-Tarjamah li-Ṭullāb: Mengajarkan Menulis dengan Menggunakan Metode Tata Bahasa dan Terjemah untuk Siswa - Hasyim Asy'ari; Elok Rufaiqoh; Husnul Majid (STAI Nurul Huda Kapongan Situbondo, 2024)
The use of the grammar and translation method in teaching Arabic offers numerous benefits. It helps students develop their writing skills, enhances memory, expands Arabic vocabulary, simplifies translation processes, clarifies sentence structures, and aids in essay writing. Additionally, this method indirectly encourages students to practice speaking and writing in Arabic through reading texts from textbooks. Research findings reveal that second-grade students at Qadri 1 Jember Model Junior School exhibit excellent memorization abilities, demonstrated during each Arabic language lesson. This method supports the development of students' writing skills through stages such as dictation of moveable content, perspectives, and tests. Beyond achieving spelling accuracy, students also enhance their ability to construct learning in Arabic. The method makes grammar and morphology comprehension easier, aiding sentence positioning and translation between Arabic and Indonesian. However, a notable consequence is the rapid explanation of materials by teachers within a limited timeframe